Pengaruh Terapi Mewarnai Sebagai Intervensi Nonfarmakologis Terhadap Tingkat Kecemasan Anak Usia 3–12 Tahun yang Menjalani Kemoterapi Kanker - Nur Awliya Hidayati; Endang Suartini (Journal of Midwifery and Health Research, 2026)
Background: Chemotherapy is a treatment administered to cancer patients and can be an unpleasant experience that triggers anxiety in children. This anxiety can affect the treatment process and therefore requires management. Colouring therapy is a form of therapeutic play that provides children with an opportunity to express their feelings comfortably and helps reduce anxiety whilst undergoing chemotherapy. Objective: This study aims to determine the effect of colouring therapy on anxiety levels in children aged 3–12 years undergoing chemotherapy. Methods: This study employed a quantitative method with a quasi-experimental design using a one-group pretest-posttest approach, with a sample of 39 respondents selected using purposive sampling. The study was conducted from January to June 2025 at the RCBADAK Cancer Shelter Foundation in Tangerang City. The instrument used was the Hamilton Anxiety Rating Scale (HARS), and data analysis employed the Paired Sample T-Test. Results: The results indicated a reduction in anxiety levels following the intervention, with a p-value of 0.000 (p < 0.05), signifying a significant difference between pre- and post-colouring therapy. Conclusion: It can be concluded that colouring therapy has a significant effect on reducing anxiety levels in children undergoing chemotherapy and can be used as a non-pharmacological intervention